2019
DOI: 10.14807/ijmp.v10i8.1045
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemo-magneto abrasive flow machine setup fabrication and experimental investigation of the process alongwith mathematical modeling and optimization

Abstract: In abrasive flow machining, there are two sets of piston-cylinder arrangements, i.e. machine and media. the machine ram pushes the media piston two and fro so that media filled inside it flows past the inner wall of workpiece and the material is removed. The extrusion pressure is the main mechanism of material removal. Various authors have made the process more effective in terms of material removal and surface roughness by providing rotational and magnetic force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been concluded that this hybrid process gave material removal 0.17gm at 4 and 5 mm rod size and 0.125 gm at 6 mm rod size. It also found that silicone rubber-based media gave maximum MRR and polyborosiloxane gave less material removal as compared to other media [67].…”
Section: Progressive Outlook On the Integration Of Electrochemical Af...mentioning
confidence: 90%
See 1 more Smart Citation
“…It has been concluded that this hybrid process gave material removal 0.17gm at 4 and 5 mm rod size and 0.125 gm at 6 mm rod size. It also found that silicone rubber-based media gave maximum MRR and polyborosiloxane gave less material removal as compared to other media [67].…”
Section: Progressive Outlook On the Integration Of Electrochemical Af...mentioning
confidence: 90%
“…Fig.26. Shows the improvement in the surface finish before and after (a) internal passage within the turbine engine diffuser[67], (b) medical implants[68], (c) finishing of helical gear[27] and (d) knee joint implant before and after finishing[23].…”
mentioning
confidence: 99%